ANALISIS ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) PEMERINTAH KABUPATEN LUMAJANG TAHUN ANGGARAN 2008 - 2012 - Sugianto, Edi (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2014)
To realize the spirit of regional autonomy, the management of Regional Budget (APBD) has to pay attention to the principle of effectivity, efficiency, and independent finance.Â The purpose of this study is to analyze the level of effectivity, efficiency, and independent finance in management of Regional Government ofÂ Lumajang in 2008 up to 2012. The study uses the analysis of : effectifity, efficiency, and independent bugdet. The data used is secondary data which is got from Dinas Pengelola Keuangan Daerah Kabupaten Lumajang by using technique of collecting data in the from of documentation. The result shows that the level of Regional Bugdet in Lumajang is very effective, but it still has low efficiency and very low independent.